We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
57
1
avatar+565 

Solve the following system:

 Apr 22, 2019
 #1
avatar+100483 
+2

x + 2y  = 4    (1) 

2x - y  = -7  ⇒   y  = 2x + 7   ( 2)

 

Sub (2) into (1)  for y

 

x + 2 [2x + 7]  = 4

x + 4x + 14  = 4

5x + 14  = 4      subtract 14 from both sides

5x = -10            divide both sides by 5         

x = -2

 

So....using (2).....y  = 2(-2) + 7  =  3

 

So....the last equation becomes

 

-2 + 3 + z  = - 4

1 + z  = -4      subtract 1 from both sides

z  = - 5

 

{x, y, z }  =  { -2, 3, - 5}

 

 

 

 

cool cool cool

 Apr 22, 2019

36 Online Users

avatar
avatar
avatar